2014
DOI: 10.3171/2014.7.peds13376
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric brainstem hemorrhages after traumatic brain injury

Abstract: Traumatic brain injuries afflict a large number of pediatric patients. The most severe injuries lead to increased intracranial pressure and herniation, with resultant changes in the brainstem. Traumatic brainstem hemorrhages have previously been associated with poor neurological outcome and fatality. However, this report discusses 2 pediatric patients who sustained severe head trauma with subsequent brainstem hemorrhages, and yet experienced good neurological outcome; the possible mechanism is describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…[12][13][14] Nevertheless, similar to previous reports, we have demonstrated that not all patients with DAI, including those with brainstem DAI, have an unfavorable outcome. 12,17,18 About 17% (95%CI 9-45) and 11% (95%CI 2-43) of our patients who had DAI in any brain regions and brainstem DAI, respectively, indeed turned out to have a favorable outcome at 18-months. As such, our results would suggest that clinicians should be prudent not to rely on the presence of DAI or brainstem DAI alone to prognosticate the outcome of their patients with severe TBI.…”
Section: Discussionmentioning
confidence: 70%
“…[12][13][14] Nevertheless, similar to previous reports, we have demonstrated that not all patients with DAI, including those with brainstem DAI, have an unfavorable outcome. 12,17,18 About 17% (95%CI 9-45) and 11% (95%CI 2-43) of our patients who had DAI in any brain regions and brainstem DAI, respectively, indeed turned out to have a favorable outcome at 18-months. As such, our results would suggest that clinicians should be prudent not to rely on the presence of DAI or brainstem DAI alone to prognosticate the outcome of their patients with severe TBI.…”
Section: Discussionmentioning
confidence: 70%
“…Recently the contribution of brain plasticity has been also invoked to explain the good recovery of 2 pediatric cases with traumatic brain injury. 1 In conclusion, DTH may represent an unusual complication in the management of trapped fourth ventricle. Endoscopic aqueductoplasty, whenever feasible, should be preferred to multiple shunting procedures to avoid the risk of differential pressure between the supratentorial and infratentorial compartment, which is the pathogenetic mechanism of this complication.…”
Section: Discussionmentioning
confidence: 91%
“…2 This results in secondary brainstem hemorrhages with a peculiar distribution in the rostral midbrain and in the ventral portion of the pons, presenting in a delayed fashion, that are termed Duret hemorrhages. 1,8,17 The pathogenesis of Duret hemorrhages has been hypothesized to consist of 2 mechanisms, stretching and disruption of small central perforating arteries or compression of small rostral draining veins, both ensuing from the abrupt descent of the brainstem against the basilar artery, which is relatively immobilized by the circle of Willis. 23 In the present case, the posthemorrhagic and postinfectious etiology of the hydrocephalus may have contributed to the arachnoidal scarring and relative immobilization of the basilar artery.…”
Section: Discussionmentioning
confidence: 99%
“…AEP wave III represents the cochlear nucleus which is located in the pontomedullary junction of the dorsolateral brainstem [ 35 ]. It is well known that brainstem lesions are associated with poor neurological outcome and fatality [ 36 ]. This finding could be reproduced in this study: Subjects with brain stem lesions on one or both sides showed a worse functional outcome from neurological early rehabilitation.…”
Section: Discussionmentioning
confidence: 99%